Amelie - Tautou, Audrey, 1976-; Debbouze, Jamel, 1975-; Kassovitz, Mathieu, 1967-; Pinon, Dominique, 1955-; Moreau, Yolande, 1953-; Deschamps, Jean-Marc; Ossard, Claudie; Laurant, Guillaume; Jeunet, Jean-Pierre, 1953- (Miramax, 2011)
At a tiny Parisian cafe, the adorable yet painfully shy Amelie accidentally discovers a gift for helping others. Soon Amelie is spending her days as a Cupid, guardian angel, and all-around do-gooder. But when she bumps into a handsome stranger, will she find the courage to become the star of her very own love story?